1983
DOI: 10.1084/jem.158.3.649
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms regulating IgA class-specific immunoglobulin production in murine gut-associated lymphoid tissues. II. Terminal differentiation of postswitch sIgA-bearing Peyer's patch B cells.

Abstract: It is now well established that Peyer's patches (pp)l are lymphoid follicles that give rise to cells that are committed to IgA development and that ultimately localize in mucosal areas (1-5). However, the mechanisms governing such commitment are not completely understood. On the one hand, PP B cells and their clonal progeny could represent a class of B cells that secrete IgA, because they are exposed to a particular kind and pattern of specific (antigenic) and/or nonspecific (T cell and/or B cell) stimuli (6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(44 citation statements)
references
References 26 publications
2
41
0
1
Order By: Relevance
“…Considerable numbers of T cells of the helper phenotype coexist with B cells, and the processes of Ia-positive follicular dendritic cells are prominent in the germinal centers (20). This suggests that the germinal center is the site of immune responses to the antigens in the intestinal lumina, and of class switching from IgM to IgA of the patch B cells (22). Antigen-trapping by follicular dendritic cells and T cell regulation of B cell maturation have been well-documented (22,50).…”
Section: Peyer's Patches Lyiiiphoepithelial Cell Layer Over Peyer's Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable numbers of T cells of the helper phenotype coexist with B cells, and the processes of Ia-positive follicular dendritic cells are prominent in the germinal centers (20). This suggests that the germinal center is the site of immune responses to the antigens in the intestinal lumina, and of class switching from IgM to IgA of the patch B cells (22). Antigen-trapping by follicular dendritic cells and T cell regulation of B cell maturation have been well-documented (22,50).…”
Section: Peyer's Patches Lyiiiphoepithelial Cell Layer Over Peyer's Pmentioning
confidence: 99%
“…The germinal center in Peyer's patch plays an important role in activation, proliferation, and heavy chain class switching during B cell responses (22). These primed or activated B lymphoblasts migrate to the mesenteric lymph node via the thoracic duct to the general circulation, and repopulate the intestinal mucosa (24).…”
Section: Peyer's Patches Lyiiiphoepithelial Cell Layer Over Peyer's Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence that T cells regulate isotype differentiation at the level of naïve murine B cells comes from several sources. Kawanishi et al [143,144] demonstrated that sIgM + sIgA -B cells could be induced to switch sIgA + B cells in the presence of T cell clones derived from GALT. These sIgA + B cells could then be induced to secrete IgA in the presence of additional exoge-nous lymphokine [142].…”
Section: Role Of Peyer's Patch Cells In Immunoglobulin Isotype Regulamentioning
confidence: 99%
“…It is known that luminal antigen is taken up by specialized surface epithelial cells which overlie Peyer's patches, the appendix and isolated lymphoid follicles in the gut [3,4], This material stimulates underlying B lym phoblasts (which are enriched with precur sors for developing an IgA isotype). These cells leave the gut-associated lymphoid tis sues and migrate in turn to the mesenteric lymph nodes, the thoracic duct and eventu ally lodge in the spleen where they undergo some degree of maturation [5][6][7][8], During their maturation, they come under the in fluence of switch T cells which encourage the B lymphocytes to alter their isotype from pto a-heavy chain [9], Also, helper T cells which augment the IgA response are known to enhance the production of cells commit ted to IgA synthesis [10]. These B cells then travel to a variety of mucosal surfaces in cluding the gastrointestinal tract, bronchial mucosa, mammary glands and salivary glands.…”
Section: Trafficking Of Gut-associated Lymphoid Cellsmentioning
confidence: 99%